Challenges of the Distinction Criteria between Evident Deception and Grosser Fraud in the Unanimous Verdict of 821 from a Legal-Economic Standpoint - Seyed Hasan Hosseinimoghadam; Hossein Hamzeh Robati (دانشنامه حقوق اقتصادی, 2025)
Maintaining economic balance in reciprocal contracts is one of the main emphases of contract law. It is common in the reciprocal contracts that the parties take away and void the option of gross fraud from themselves. According to the unanimous verdict No. 821 of the General Board of the Supreme Court, depriving the option to evident deception is other than the highest level of fraud, which is traditionally considered "grosser". But one of the substantial challenges that the courts and the claimant of evident deception or grosser fraud also face in dealing with the settlement of the lawsuit arising from lesion, is how to identify evident fraud from the grosser one and its criteria. In Article 417 of the Civil Code, the criterion for identifying lesion has been assigned to customary arbitration. So, if lesion is not negligible according to custom, this lesion is considered gross. Nevertheless, based on the criterion of this article, to distinguish between evident and grosser deception, it is necessary to refer to the governing custom. In addition to the fact that customary arbitration and the absence of specific and detailed criteria cause the courts' personal preferences and ideas to enter into the acceptance or non-acceptance of lesion happened according to the circumstance in the real world, but also customary arbitration and the influence of judges' personal taste in recognizing gross deception and grosser lesion damage the contractual stability and the economic balance of the parties and the contract. Therefore, the customary criterion is one of the most challenging cases in the diagnosis of lesion. On the other hand, by accepting the customary criteria, the question under discussion is whether the customary arbitration is based on generic or subjective criteria? If custom usually differentiates between evident deception and grosser lesion, is it based on the type of people and wise people or based on the type of transactions in normal conditions? If the standard of custom is subjective, Will the criterion of custom for distinction be based on the status of the parties to the contract or the terms and subject matter of the transaction that is alleged to be lesion? According to articles 415, 416, 417 and 418 of the civil law, it seems that the standard of custom should be considered as a combination of a generic standard and a subjective standard in order to draw a realistic standard for distinguishing evident deception and grosser fraud, and in order to maintain the economic balance of the parties, which some people refer to as "present custom".